AIR REBUSAN JAHE MERAH DAN AIR KELAPA TERHADAP INTENSITAS NYERI DISMENORE PADA REMAJA PUTRI - Agustina Sari; Eva Syaripah; Fajar Oktaviani (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2024)
It is very important to treat dysmenorrhea, especially in teenagers, because if it is not treated it will affect the teenagers' own activities. The impact that arises from dysmenorrhea is the feeling of discomfort that women feel every time they menstruate, problems with the reproductive system can arise. To find out the comparison of the effectiveness of consuming red ginger boiled water and coconut water on the intensity of dysmenorrhea pain in young women at MTS Almarfuiyah in 2023. This research uses qualitative methods with a case study approach. This activity is carried out on young women who experience dysmenorrhea. In this study, the sample consisted of 2 people, where 1 sample used the intervention of consuming red ginger boiled water and 1 sample used green coconut water. The research instrument used to collect data is the data collection tool in this research using the Numeric Rating Scale (NRS) observation sheet. The study used univariate analysis to describe the comparison of the effectiveness of consuming red ginger boiled water and a mixture of coconut water on the intensity of dysmenorrhea pain in young women at MTS Almarfuiyah in 2023. Based on the results of these two observations, it is known that consumption of red ginger boiled water is more effective in reducing pain levels. Dysmenorrhea is seen from 3 days of intervention from scale 7 down to scale 4 and up to scale 1, while for consumption of green coconut water seen from 3 days of intervention from scale 7 down to scale 5 and up to scale 2. Midwives can collaborate with the school to register data on female students who experience dysmenorrhea to obtain information on how to reduce pain.